2023
DOI: 10.1038/s41398-023-02426-1
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes in addiction and their neurobehavioral profiles across three functional domains

Abstract: Rates of return to use in addiction treatment remain high. We argue that the development of improved treatment options will require advanced understanding of individual heterogeneity in Substance Use Disorders (SUDs). We hypothesized that considerable individual differences exist in the three functional domains underlying addiction—approach-related behavior, executive function, and negative emotionality. We included N = 593 participants from the enhanced Nathan Kline Institute-Rockland Sample community sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…Recently, Drossel et al found that distinct subtypes of individuals with SUDs were linked to different patterns of rs-FC. In “reward-type” individuals (i.e., higher approach-related behavior), substance use was related to decreased connectivity in the FPN and SN, while in “cognitive-type” (i.e., lower executive function), substance use was related to increased connectivity in the FPN and SN [ 36 ]. This suggests that different individuals have distinct neurobiological pathways contributing to their craving.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Drossel et al found that distinct subtypes of individuals with SUDs were linked to different patterns of rs-FC. In “reward-type” individuals (i.e., higher approach-related behavior), substance use was related to decreased connectivity in the FPN and SN, while in “cognitive-type” (i.e., lower executive function), substance use was related to increased connectivity in the FPN and SN [ 36 ]. This suggests that different individuals have distinct neurobiological pathways contributing to their craving.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with deficits in working memory may include adults characterized by inattention or distractibility. This differs from individuals who have response inhibition difficulties, who are typically characterized as more impulsive (Drossel et al, 2023). Similarly, distractible or impulsive individuals often differ from those with set shifting difficulties, who are often characterized as perseverative and exhibiting a 'stickier' personality style (Alexopoulos et al, 2015;Voon, 2015).…”
Section: Individual Differences In Cognitive Control and Emotion Regu...mentioning
confidence: 99%
“…This takes into account different theoretical perspectives including for example genetics and social environmental variables which clearly have a significant role in explaining, understanding and treating addiction (Volkow et al, 2016 ). As well as this more inclusive approach, the scientific literature has shifted its focus toward the individual both in respect to understanding addiction and to treating addiction (Drossel et al, 2023 ). Further to this, as clearly expressed in this Research Topic, understanding addiction is evolving.…”
mentioning
confidence: 99%